2020
DOI: 10.1093/humupd/dmz048
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pregnancy loss: diagnostic workup after two or three pregnancy losses? A systematic review of the literature and meta-analysis

Abstract: A search for RPL was combined with a broad search for terms indicative of number of pregnancy losses, screening/testing for pregnancy loss or the prevalence of known risk factors. Meta-analyses were performed in case of adequate clinical and statistical homogeneity. The quality of the studies was assessed using the Newcastle-Ottawa scale.OUTCOMES: From a total of 1985 identified publications, 21 were included in this systematic review and 19 were suitable for meta-analyses. For uterine abnormalities (seven stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 46 publications
2
64
0
9
Order By: Relevance
“…In the present study, 14 signaling pathways and 13 genes were identified by enrichment analysis, and 5 of the 13 genes overlapped with the hemoglobin assembly results. One of the consequences of meiosis failure is triploidy, which is a relatively common cause of miscarriage and RPL [40]. The identification of six genes enriched in six signaling pathways in the present may thus be associated with RPL.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, 14 signaling pathways and 13 genes were identified by enrichment analysis, and 5 of the 13 genes overlapped with the hemoglobin assembly results. One of the consequences of meiosis failure is triploidy, which is a relatively common cause of miscarriage and RPL [40]. The identification of six genes enriched in six signaling pathways in the present may thus be associated with RPL.…”
Section: Discussionmentioning
confidence: 69%
“…RPL was defined as three or more miscarriages. 21 Patients suffering from endocrine and autoimmune diseases, uterine malformation such as septate uterus, multiple myoma, endometrial polyp detected by hysteroscopy, hydrosalpinx detected by ultrasonography or adenomyosis with over a uterine wall >2.5 cm thick at the time that hysteroscopy was performed in order to diagnose CE were excluded from this study. [22][23][24][25][26][27][28][29] Patients who had received ≥7 days of antibiotics for CE treatment were also excluded.…”
Section: Subjectsmentioning
confidence: 99%
“…RIF was defined as the failure of clinical pregnancy after 4 good quality embryo transfers, with at least three fresh or frozen IVF cycles, as per Coughlan et al [19]. RPL was defined as the patient with 3 or more miscarriage [20].…”
Section: Methodsmentioning
confidence: 99%